RESISTANCE BEYOND THE THEME: AN ANALYSIS OF THE PRESENCE OF THE ANTI-ETHOS IN AQUARIUS - Klem Lima, Kárin; Arruda de Moura, Sérgio (LINKSCIENCEPLACE, 2026)
This article intends to study the meaning effects generated by the incorporation of a critique excerpt made by the journalist Reinaldo Azevedo in the promotional poster of the movie Aquarius, released in 2016. The controversy generated by the presence of this statement in the poster stimulates the discussion about how the cinema can be considered a device to construct portraits of contemporary Brazilian society and how their discourses can surpass the narrative, acquiring a symbolic dimension that reaches beyond the movie screen. To discuss these issues, the article will conduct a discussion about the film and the related controversial episodes reported in the media. On the following, it will analyze how Veja and its columnist Reinaldo Azevedo have approached these episodes. For the conclusion, it will analyze the movie promotional poster and the discursive effects generated by the presence of the journalist's quote on the piece.